Associations of Blautia Genus With Early-Life Events and Later Phenotype in the NutriHS - Freitas, Renata G. Borges de Oliveira Nascimento; Vasques, Ana Carolina J.; Fernandes, Gabriel da Rocha; Ribeiro, Francieli B.; Solar, Isabela; Barbosa, Marina G.; Pititto, Bianca de Almeida-; Geloneze, Bruno; Ferreira, Sandra Roberta G. (Frontiers in Cellular and Infection Microbiology, 2022)
Early-life events are associated with risk of obesity and comorbidities later in life. The gut microbiota – whose composition is influenced by genetics and environmental factors – could be involved. Since the microbiota affects metabolism and fat storage, early-life insults could contribute to the occurrence of obesity driven, in part, by microbiota composition. We examined associations of gut bacteria with early-life events, nutritional status, and body composition in the NutriHS. Methods: A cross-sectional study of 114 female participants examining early-life data, body composition and biological samples was conducted. Fecal microbiota structure was determined targeting the V3–V4 region of the 16S rRNA gene. PCoA and PERMANOVA were used to test the impact of variables on microbial diversity. Profiles were identified using the Jensen-Shannon divergence matrix and Calinski–Harabasz index. Differential abundance between the categories of exclusive breastfeeding duration and nutritional status was tested using DESeq2. Results: In the sample (median age 28 years and BMI 24.5 kg/m2), 2 microbiota profiles driven by the Blautia or Prevotella genus were identified. An estimated 9.1% of the variation was explained by the profiles (p<0.001), 2.1% by nutritional status (p=0.004) and 1.8% by exclusive breastfeeding (p=0.012). The proportion of participants with BMI <25 kg/m2 and who were breastfed for at least 6 months was higher in the Blautia profile (p<0.05). Conclusion: Findings in a Blautia-driven profile of healthy women reinforce that early-life events play a role in defining gut microbiota composition, confirming the importance of exclusive breastfeeding for infant gut colonization in establishing a protective profile against adiposity-related outcomes in adulthood.